Building Financial Resilience of Boarding House Employees Through Financial Literacy - Gulo, Niat Sevin Arni Putri; Palupiningtyas, Dyah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Inflation and post-COVID-19 economic uncertainty have placed significant financial pressure on low-income workers, including boarding house employees. This study aims to analyze the effects of financial literacy, financial attitude, and economic pressure on personal financial management behavior and financial resilience among boarding house employees in Semarang Regency. A mixed-methods sequential explanatory approach was employed, with the quantitative phase (n=150) analyzed using PLS-SEM, followed by a qualitative phase (n=15) using thematic analysis. Results indicate that financial literacy (β=0.312; p<0.01) and financial attitude (β=0.387; p<0.01) have significant positive effects, while economic pressure has a negative effect (β=-0.256; p<0.01) on financial management behavior. The model explains 52.4% of the variance in financial management behavior. Financial management behavior significantly mediates the relationship between financial literacy and financial resilience. The qualitative phase identified five adaptive strategies: strict budgeting, income diversification, strategic saving, social network utilization, and financial technology adoption. This study contributes to the literature by exploring an understudied population and integrating the economic pressure perspective into financial behavior models.